Learning Engagement; Definition, Aspects, Measurement and Intervention Strategies - Alamsyah, Muh. Nur; Nuha, Moch. Syihabudin; Muslihati, Muslihati; Zamroni, Zamroni (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2024)
This study aims to clarify the definition of learning engagement, explain the key aspects involved, explore relevant measurement tools, and investigate interventions that can increase students' engagement levels. An in-depth understanding of learning engagement is expected to positively contribute to the improvement of the education system and the development of students' potential more holistically. This research is a literature review that aims to identify relevant articles and literature sources that can contribute to answering the research questions regarding the concept of learning engagement. Learning engagement is part of student engagement, which includes aspects of student involvement in the learning process, both cognitively, behaviorally, and affective. Thus, student engagement is the foundation for the creation of student engagement, which includes students' commitment and active participation in the learning process. It is important to develop programs that are comprehensive and adaptable to the unique needs of students. While universal interventions are beneficial, targeted programs can be more effective for high-risk students. Therefore, it is necessary to implement interventions at various levels, including universal programs for general students and more selected services for at-risk students.